Monitoring of meteorological variables through a wireless data acquisition system - Ruiz-Ayala, Daniel Camilo; Vides-Herrera, Carlos Arturo; Pardo-García, Aldo (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In this article we present the development of a system for the wireless monitoring of climatic variables. The design was made from microchip microcontrollers, which perform the acquisition, storage and wireless transmission of digital signals. Likewise, the microcontroller uses a clock in real time to know the date and time of acquisition of the samples. The hardware also has five channels for connecting sensors and a Micro SD memory for storage of data, along with a Wi-Fi module for wireless monitoring of variables. The information is uploaded to a server that hosts the web page, designed to view the data from any computer with an internet connection. Additionally, an Android application was developed that allows data to be viewed from mobile devices with that operating system.  The performance of the system was satisfactory, after comparing the data acquired with those of two commercial meteorological stations, which served as a pattern. It is concluded that microcontrollers continue to be adequate devices to implement data acquisition systems, which when combined with customized applications, provide competitive solutions at a reasonable cost.